Unveiling the “Whys” of Japanese Third-age Learners’ English Language Proficiency - Dominic Bryan S. San Jose; Melona Q. Guitche; Dennis V. Madrigal (Philippine Social Science Journal)
Japanese third-age English language learners, though growing, are still an under-researched demographic. Grounded on the quantitative results of Japanese third-age learners' English language proficiency (ELP), which is B1 on average, this descriptive-qualitative study explored why the participants got certain levels of ELP. Using the maximum variation sampling, the researchers chose five third-aged Japanese participants from the five cities of Aichi, Japan. The findings reveal two significant themes: motivational factors (with three sub-themes: personal interest, social engagement, and personal enrichment) and factors affecting ELP (with four sub-themes: dynamics of sex and ELP, dynamics of age and ELP, dynamics of education and ELP, dynamics of time and ELP), encourage the examination of learning a language as a means to greater autonomy, cultural sensitivity, and an understanding of the global community. It provides valuable insights for teachers or curriculum designers to improve EFL programs for third-age learners, enhancing accessibility, interest, and effective language acquisition.